2014
DOI: 10.1016/j.joca.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical cartilage imaging techniques at 3 T MRI

Abstract: CEST is able to detect normal and damaged cartilage and is non-inferior in distinguishing both when compared to dGEMRIC and T2 mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 56 publications
9
87
1
Order By: Relevance
“…Here it was obvious that a severe OA could be detected with SE-sequences up to 94% and mild osteoarthritis could be discovered in 10% of the specimen [111]. In several other studies different MRI sequences were used to detect cartilage degeneration [15,116,117]. It was confirmed that even after MRI examinations with FLASH and DESS sequences low correlation in terms of sensitivity and specificity was found for both sequences in normal to mild Mankin grades [112].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here it was obvious that a severe OA could be detected with SE-sequences up to 94% and mild osteoarthritis could be discovered in 10% of the specimen [111]. In several other studies different MRI sequences were used to detect cartilage degeneration [15,116,117]. It was confirmed that even after MRI examinations with FLASH and DESS sequences low correlation in terms of sensitivity and specificity was found for both sequences in normal to mild Mankin grades [112].…”
Section: Discussionmentioning
confidence: 99%
“…Development and grading of OA is mainly determined by histological analyses [4,6,14]. In humans, grade and prevalence of OA may be detected by MRI scanning [15,16] and through X-ray examination [17]. Thus, correlation of histological changes and MRI scanning is needed in diagnosis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain dGEMRIC images, a 3D T 1 ‐weighted VIBE sequence with two excitation flip angles (5° and 26°), TR/TE 15/2.63 msec, voxel size 0.4 × 0.4 × 3 mm 3 , field of view (FOV) 140 × 140 mm 2 , imaging matrix 384 × 384, echo train length: 1 and total acquisition time of 5:24 minutes was performed based on similar protocols at the knee before (t = 0) and after (see timepoints below) intravenous administration of a double dose of gadopentetate dimeglumine (0.2 mmol/kg of Gd‐DTPA, Magnevist, Berlex Laboratories, Wayne, NJ). After Gd‐DTPA administration the subjects moved their wrist for 5 minutes in all directions, as exercise has been shown to increase contrast agent delivery to the joint .…”
Section: Methodsmentioning
confidence: 99%
“…Shorter T2 values were found at higher field strengths [24]. In addition, the sequence type, coil architecture and calculation method of T2 mapping affect the T2 result [11].…”
Section: Discussionmentioning
confidence: 99%